A holistic approach is needed for women with an inflammatory arthritis in the different phases around pregnancy; the results of the CAPRI study - van Steensel – Boon, A. J.; Wintjes, H. M.; Röder, E.; Smeele, H. T. W.; Kranenburg - van Koppen, L. J. C.; Dolhain, R. J. E. M.; Perez-Garcia, L. F. (Frontiers in Global Women's Health, 2025)
IntroductionWomen with inflammatory arthritis (IA) face significant challenges throughout preconception, pregnancy, and postpartum phases, including concerns about disease management and medication safety. The Reproductive Rheumatology care pathway at Erasmus University Medical Center integrates specialized care from rheumatologists and specialized nurses to address both medical, nursing, practical and emotional needs during these phases. This study evaluates patient satisfaction, identifies unmet needs, and explores opportunities for enhancing support within this integrated care model.MethodsThis was a cross-sectional study. We designed a customized questionnaire for women 18 years and older who were treated following the Reproductive Rheumatology care pathway and had given birth between 2019 and 2021. These women were invited to fill in the questionnaire. The survey assessed satisfaction with care, challenges experienced, and information needs across preconception, pregnancy, and postpartum phases. Descriptive statistics and paired t-tests were used for data analysis.ResultsParticipants reported high satisfaction with care, rating rheumatologists an average of 8.8/10 and specialized nurses 9.2/10. While 78.9% experienced no major issues, some faced problems such as managing disease flares and difficulties around conception. Information needs varied by phase: preconception needs focused on medication safety and fertility, while pregnancy and postpartum concerns included disease management and emotional support. Specialized nurses were pivotal in offering personalized care and practical advice.ConclusionThe integrated Reproductive Rheumatology care pathway effectively supports women with IA through their reproductive journey. Despite high satisfaction, improvements could be made in personalized care and addressing challenges related to confidence and help acceptance. Future research should investigate the long-term impact of such care pathways on reproductive outcomes and patient well-being.